Contribution of Leasehold Forests in Reducing Income Inequality - Sharma, Bishnu Prasad (Economic Journal of Development Issues, 2016)
Structural transformation in the economy and institutional innovations bring changes in the socio--economic dynamics in the society. This leads to changes in the pattern of income distribution, poverty and income inequality. Environmental resources such as forest still make significant contribution in rural household economy. The leasehold forestry program for the poor introduced in the last decade of 2000 with the purpose of forest regeneration and raising household income in Nepal has completed more than two decades. Using micro data collected at household level from two districts in Nepal in 2008, this paper examined the contribution of leasehold forest and other sources in household economy. The study finding revealed that all biomass income sources including agriculture and wage work had income inequality reducing effects measured in terms of Gini-coefficient. In contrast, remittance and salary and business income had inequality raising effects. As leasehold forest contributed less than 5 percent of the household income even after 10 years of investment, there is a strong need to improve its performance by integrating it with income generating activities such as livestock and agroforestry. The inequality raising effect ranging from 3 to 6 percent from various biomass sources needs to be better utilized.Economic Journal of Development Issues Vol. 17 & 18 No. 1-2 (2014) Combined Issue, Page: 29-28